Use of the amniotic membrane to cover the peritoneal cavity in the reconstruction of the abdominal wall with polypropylene mesh in rats - Barbuto,Rafael Calvão (2015)
OBJECTIVE: to evaluate the efficacy of the amniotic membrane used with polypropylene mesh against the formation of adhesions and its influence on healing. METHODS: twenty five female Wistar rats were anesthetized for creating a parietal defect in the anterior abdominal wall. Its correction was made with polypropylene mesh alone and associated with amniotic membrane. In the control group (n=11), the screen was inserted alone. In group A (n=7) we interposed the amniotic membrane between the screen and the abdominal wall. In group B, the amniotic membrane was placed on the mesh, covering it. After seven days, the animals were euthanized for macroscopic and microscopic evaluation of healing. RESULTS: adhesions were observed in all animals except one in the control group. Severe inflammation was observed in all animals in groups A and B and in three of the control group, with significant difference between them (A and B with p=0.01). Pronounced angiogenic activity was noted in one animal in the control group, six in group A and four in group B, with a significant difference between the control group and group A (p=0.002) and group B (p=0.05). The scar collagen was predominantly mature, except in five animals of the control group, with significant difference between the control group and group A (p=0.05) and group B (p=0.05). CONCLUSION: The amniotic membrane did not alter the formation of adhesions in the first postoperative week. There were also pronounced inflammation, high angiogenic activity and predominance of mature collagen fibers, regardless of the anatomical plane that it was inserted in.